Dynamic behavior of fiber-reinforced soil under freeze-thaw cycles - Orakoğlu, Müge Elif; Liu, Jiankun; Niu, Fujun (My University, 2017)
This research presents the dynamic behavior of fiber-reinforced soil exposed to freeze-thaw cycles. The series of dynamic triaxial tests were conducted on fine-grained soil mixed with different percentages of basalt and glass fibers subjected to freeze-thaw cycles. The results showed that after freeze-thaw cycles, with the addition of basalt and glass fibers, the damping ratio and the shear modulus increased at a constant confining pressure because of the increase of stiffness, but the shear modulus decreased with increasing shear strain. Moreover, the theoretical analytical formulations were developed to define for dynamic shear stress and dynamic shear modulus. The parameters were predicted by Hardin-Drnevich model and Kondner-Zelasko model. The shear modulus was expressed as a function of freeze-thaw cycles, fiber contents, confining pressure and initial water content. Finally, ten coefficients were calibrated by analyzing the experimental results and then employed to describe dynamic shear modulus of the fiber-reinforced soil.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Fiber-reinforced soil; Dynamic test parameters; Freeze-thaw cycles; Theoretical analytical formulations